An indicator-based method supporting assessment and decision-making of potential by-product exchanges in industrial symbiosis. (20th March 2021) - Kosmol, Linda; Maiwald, Martin; Pieper, Christoph; Plötz, Joscha; Schmidt, Thorsten
Abstract: Limiting global warming and increasing resource efficiency remain central tasks of our time. In the quest for sustainable development, approaches aimed at the transition from linear to circular supply chains and networks are increasingly drawing attention in research, politics and business. Industrial symbiosis is one such approach, which aims to create ecological and economic benefits through the novel exchange of underutilized resources between processes and companies. To decide for or against the realization of potential exchanges, the compatibility of the processes and potential benefits of the exchange must be assessed in advance. Currently, however, this prospective assessment focuses primarily on the network level and on quantifiable information using absolute or relative indicators tied to specific dimensions or units. While these indicators are essential to quantify the environmental and economic impacts of resource exchanges, they are insufficient regarding compatibility measurement of the processes involved. In addition, a clear procedure for handling the indicators is rarely provided, which increases the effort for their selection, definition, and consequently for the assessment. Therefore, we propose a method that incorporates qualitative and quantitative indicators into an adaptive three-stage assessment process to first roughly estimate and later calculate the fit of different processes or companies. This procedure is intended to reduce the time and effort required for information collection and synergy assessment by industrial actors and intermediary stakeholders. The indicators represent the technical feasibility, economic viability (including managerial aspects) and environmental benefits of potential resource exchanges. Key features of the method are its guidance through the assessment, exclusion and decision-making process and the introduction of dimensionless coverage ratios to assess the technical or operational match of the entities involved. Highlights: Qualitative and quantitative indicators to assess by-product exchanges. Proposal of coverage ratios to judge the technical and operational fit of processes. Technical, economic and environmental assessment of symbiotic alternatives. Three-stage method to guide decision-making.